2009
DOI: 10.1159/000245332
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic and Angiostatic Chemokines in Idiopathic Pulmonary Fibrosis and Granulomatous Lung Disease

Abstract: Background: Angiogenesis-angiostasis balance and leukocyte recruitment are influenced by different concentrations of distinct chemokines. Objective: To investigate the relative contribution of angiogenic and angiostatic CXC chemokines to the pathogenesis of idiopathic pulmonary fibrosis (IPF) and granulomatous lung diseases, we examined the in vitro production of an angiogenic chemokine (IL-8), and 2 angiostatic chemokines (IP-10 and MIG) by alveolar macrophages. Methods: Alveolar macrophages from 16 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…Angiogenesis occurs as part of the wound healing process and it has been described around the fibroblastic foci in both IPF patients and in the bleomycin model (Cui et al, 2001; Sterclova et al, 2009). CXC chemokines are important factors in the angiogenic–angiostatic balance as well as being powerful chemoattractants for inflammatory cells (Gerard and Rollins, 2001).…”
Section: Epithelial Cell Integrins and Chemokinesmentioning
confidence: 99%
“…Angiogenesis occurs as part of the wound healing process and it has been described around the fibroblastic foci in both IPF patients and in the bleomycin model (Cui et al, 2001; Sterclova et al, 2009). CXC chemokines are important factors in the angiogenic–angiostatic balance as well as being powerful chemoattractants for inflammatory cells (Gerard and Rollins, 2001).…”
Section: Epithelial Cell Integrins and Chemokinesmentioning
confidence: 99%
“…Furthermore, several studies suggested an involvement of the chemokine CCL2 in the pathogenesis of IPF, notably through its action on resident pulmonary fibroblast and circulating fibrocytes, promoting the generation of abundant extracellular matrix in the lungs (Gharaee-Kermani et al, 1996;Phillips et al, 2004;Moore et al, 2005;Inomata et al, 2014). Such strong evidence involving CXCL8 in the pathogenesis of the disease are lacking, although this chemokine is thought to act as a pro-fibrotic factor in IPF via the promotion of exacerbated angiogenesis (Strieter et al, 2002;Rosenkilde and Schwartz, 2004;Antoniou et al, 2006;Martina et al, 2009;Cui et al, 2010). In dogs, mRNA expression of CXCL8 and CCL2 was found to be increased in CIPF lungs compared with controls .…”
Section: Cxcl8 and Ccl2 Concentrationsmentioning
confidence: 99%
“…Therefore, the aim of the present study was to compare basal circulating blood concentrations of four molecules of interest obtained in healthy dogs from seven breeds differently predisposed to CIPF. Selection of molecules studied was based on their potential implication into the pathogenesis of canine pulmonary fibrosis in view of data from either human or canine literature and were as follows: the chemokine (C-X-C motif) ligand 8 (CXCL8) (Cui et al, 2010;Ahn et al, 2011;Krafft et al, 2013), the chemokine (C-C motif) ligand 2 (CCL2) Moore, 2014), the serotonin (5-HT) (Konigshoff et al, 2010;Krafft et al, 2013), and the vascular endothelial growth factor (VEGF) (Ando et al, 2010;Woodcock et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…4,7,15 Many investigators confirmed the importance of the CXCR3-CXCR3 ligand axis in the mobilization of Th1 lymphocytes to the loci of inflammation. 16 The most extensively studied molecule is CXCL10. Agostini et al 7 showed that cells bearing CXCL10 were mainly epithelioid cells and CD68 + macrophages located inside the granulomatous areas.…”
Section: Abbreviations: Ns -Nonsignificantmentioning
confidence: 99%